(untitled) (Journal of Hama University, 2019)
Aim of Study: to evaluate the ability of panoramic image to determine the mesiodistal placement of orthodontic brackets compared to CBCT. Materials and Methods: Sample: consisted of 30 pts (600 teeth) aged between 18 – 25 years old. Study Method: after orthodontic brackets bonding, leveling and alignment stage had been completed by using the rounded wires. Panoramic radiographs and CBCTs were done and studied. Comparison of the accurate placement of orthodontic brackets had been carried out from 2nd premolar to 2nd premolar in both sides of both jaws through drawing the long axes of teeth and their brackets which bonded to them, then there was measuring the angle established between those two axes. Statistical study: Chi square and McNamar tests were done for frequencies differences study. Wilcoxon test was done for ranks mean differences between two groups. Results: There were no significant differences in frequencies of panoramic and CBCT results (P=0.775). Whereas, there was a significant difference in the ranks means between two groups (P=0.000) which means shows that the panoramic image could not determine the actual value of the angle established between tooth axis and the axis of its brackets. Conclusion: Panoramic radiography can be a useful tool but not absolutely accurate during brackets bonding if we want it to get satisfying results for orthodontic patients